Caracterização de um novo modelo de microtecido obtido a partir do cultivo tridimensional de fibroblastos e sua utilização na avaliação dos efeitos citotóxicos do veneno total de Bothrops erythromelas - Andrade, Felipe Rhaynan da Silva Andrade (2023)
The three-dimensional culture of cells comprises a set of techniques that have gained notoriety in recent years due to their robustness. The objective of this study was to standardize the three-dimensional culture of fibroblasts using agarose microchips as anchoring material and to use the developed model to perform treatments with the total venom of Bothrops erythromelas and its respective antivenom. The MRC-5 and L929 fibroblast cell lines were cultured at increasing cell densities (5 × 104, 105, and 1.5 × 105 cells/chip for MRC-5 and 1.25 × 104, 2.5 × 104, and 5 × 104 cells/chip for L929). Morphometric parameters were evaluated through images obtained from an inverted microscope: solidity, circularity, and Feret diameter. The L929 cell line showed better morphometric results, with more regular growth parameters, and was chosen for further experiments. The viability of the microtissues was assessed using the acridine orange and ethidium bromide staining method, which showed viable cells in the microtissues on days 5, 7, and 10 of cultivation. Histochemical and histological analyses were performed, including hematoxylin/eosin staining, which showed a good structure of the spheroids. Alcian blue staining revealed a small amount of acid proteoglycans. Picrosirius red staining showed a scarcity of collagen, and finally, immunohistochemical analysis with ki-67 showed different patterns of cell proliferation depending on the cultivation day. The microtissues were also subjected to pharmacological tests using the total venom of B. erythromelas at concentrations of 12.5 µg/mL and 25 µg/mL for 24 hours, along with its antivenom (AV) at a ratio of 5:1. The results showed that the venom was not cytotoxic in either the traditional or three-dimensional models, but it caused morphological changes in both forms of cultivation. The cells in a monolayer lost their shape and size, and the microtissues showed cell detachment, losing their structure. The antivenom was able to prevent the actions of the venom. Thus, this study showed that the L929 cell line is capable of presenting stable three-dimensional growth. It also demonstrated that the generated microtissues have potential for use in pharmacological experiments.